156k views
1 vote
Solve the equation using the distributive property abd properties of equality -(a + 3)= -55

User Chax
by
4.6k points

2 Answers

4 votes

Final Answer:

a = 52

In-depth explanation:

Hi! The question is asking us to solve the equation, which is:


\large\textbf{-(a + 3) = -55}

Distribute the minus:


\large\textbf{-a - 3 = -55}

Add 3 to each side:


\large\textbf{-a = -55 + 3}


\large\textbf{-a = -52}

Divide each side by -1. The result is:


\large\textbf{a = 52}

∴ a = 52

User Manjit Kumar
by
4.7k points
0 votes

Answer:

a=52

Explanation:

-(a + 3)= -55

-(a) + -(3)= -55

-a - 3 (+3) = - 55+3

-a -3(+3) = -52

-a = - 52

a=52

or

-(a + 3)= -55

(a + 3)= 55

(a) + (3)= 55

a + 3(-3)= 55(-3)

a = 52

User Knells
by
5.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.